Economics of milk production and factors affecting milk yield in Meghalaya: Estimating the seasonal effect - Sheikh, Feroze Mohammad; Singh, Ram; Sirohi, Smita (Indian Journal of Dairy Science, 2019)
This paper estimated the effect of season on milk yield and cost of milk production in Meghalaya, a state located in the North Eastern hill region of India. Primary data were collected from 300 randomly selected dairy farmers in three different seasons during 2013-14. It was found that a herd was composed of 2.27 crossbreds and 1.20 local milking cows in the study area. The net maintenance cost was highest in the month of winter in case of local cows (75) and in the month of rainy season in case of CBs (167) whereas, minimum in summer season for both local (68) and CB (151) cows. The net returns per litre of milk were negative for local cows whereas, it were positive for crossbreds; highest being in rainy season and lowest in the summer season. The amount of labour and green fodder have positive, but the stage of lactation has negative and significant effect on the milk yield across the seasons. The milk yield in rainy and winter season was significantly higher than the summer season. The ANCOVA model indicated significant effect of season on milk yield of in milk cows in the study area.